Identification of novel phenotypes in pediatric sepsis based on blood glucose trajectories - Wang, Ying; Song, Wanqin; Li, Shaojun; Xu, Xianming; Liu, Wenjun; Liu, Chengjun; Xu, Feng; Li, Jing (Frontiers in Pediatrics, 2025)
ObjectiveMetabolic heterogeneity in sepsis is a critical determinant of prognosis. This study applied group-based trajectory modeling (GBTM) to identify blood glucose trajectory phenotypes in pediatric sepsis and elucidate their associations with clinical outcomes.MethodsA retrospective cohort study was conducted, enrolling 1,178 pediatric patients diagnosed with sepsis who were admitted to the pediatric intensive care unit of the Children's Hospital of Chongqing Medical University between 2014 and 2022. Dynamic blood glucose data were collected within 72 h of ICU admission, and GBTM was employed to classify trajectory phenotypes. Multivariate logistic regression was used to identify independent predictors of in-hospital mortality. A subgroup analysis focused specifically on patients with septic shock.ResultsThe analysis identified four distinct blood glucose trajectory phenotypes: Group 1 (7.3%): Slow-recovery hypoglycemia, predominantly among infants with severe liver injury, coagulopathy, and hyperlactatemia (in-hospital mortality: 13.79%). Group 2 (59.9%): Normoglycemia with minimal organ dysfunction (reference group; mortality: 5.10%). Group 3 (27.7%): Persistent mild hyperglycemia, characterized by elevated inflammatory markers and mild organ injury (mortality: 8.26%). Group 4 (4.9%): Persistent severe hyperglycemia associated with renal impairment and lactate accumulation (mortality: 17.24%). Multivariate analysis revealed Group 4 as an independent risk factor for mortality (aOR = 3.13, 95% CI 1.38–7.07). In the septic shock subgroup, the mortality risks for Group 1 and Group 4 increased by 5.2-fold and 8.28-fold, respectively (both P < 0.05).ConclusionGBTM effectively stratifies pediatric sepsis into distinct blood glucose trajectory phenotypes. Persistent severe hyperglycemia (Group 4) independently predicts in-hospital mortality, while slow-recovery hypoglycemia (Group 1) indicates a poor prognosis in septic shock. Phenotype-guided interventions are recommended: early insulin therapy (target blood glucose <10 mmol/L) for Group 4 and prophylactic glucose infusion (target >3.8 mmol/L) for Group 1.